A Critical Survey on Juliet: A Strong Female Character: Breaking Stereotypes: The Strength of Juliet in Shakespeare's Romeo and Juliet (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Shakespeare expressed this idea in his play which incorporated strong and rebellious woman. One of these plays that show a strong heroine is Romeo and Juliet, which are two star-crossed lovers from rival families. The main character, Juliet, not only went through a stage of self-realization but she still remained faithful to her morals and values. The character of Juliet perhaps illustrates strength in humans. Shakespeare breaks stereotypes through Juliet by staying faithful to her morals, not being obedient to traditional values, and remaining strong during risky consequences.